The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/13623613231213295
|View full text |Cite
|
Sign up to set email alerts
|

Social motor synchrony in autism spectrum conditions: A systematic review

Devyn Glass,
Nicola Yuill

Abstract: Some researchers suggest difficulties synchronising with a partner could underpin the social differences associated with Autism Spectrum Condition, potentially acting as a marker for autism. Social Motor Synchrony (SMS) is one aspect of synchrony that could augment observational diagnostic procedures. However, the full breadth of literature examining SMS in autism has not been systematically reviewed. A systematic review following the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Despite this, most synchrony studies have involved unfamiliar partnerships or have been situated in unfamiliar environments, such as university study centers (e.g., Fitzpatrick et al, 2017 ; Georgescu et al, 2020 ; Liu et al, 2021 ). Glass and Yuill (2023) found autistic pairs displayed similar synchrony to non-autistic pairs in carefully considered social contexts: in familiar settings and partnerships with personalized tasks. It remains unclear whether the lower synchrony previously observed in mixed pairs (e.g., Georgescu et al, 2020 ) is the result of an interpersonal mismatch, or whether this is influenced, and may be improved, by other contextual factors.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite this, most synchrony studies have involved unfamiliar partnerships or have been situated in unfamiliar environments, such as university study centers (e.g., Fitzpatrick et al, 2017 ; Georgescu et al, 2020 ; Liu et al, 2021 ). Glass and Yuill (2023) found autistic pairs displayed similar synchrony to non-autistic pairs in carefully considered social contexts: in familiar settings and partnerships with personalized tasks. It remains unclear whether the lower synchrony previously observed in mixed pairs (e.g., Georgescu et al, 2020 ) is the result of an interpersonal mismatch, or whether this is influenced, and may be improved, by other contextual factors.…”
Section: Introductionmentioning
confidence: 80%
“… Romero et al (2018) , for instance, found higher than chance levels of synchrony between autistic children and therapists in child-led conversations. Other studies have shown that synchrony between pairs of autistic children can equal synchrony between pairs of non-autistic children when the settings and partners are familiar, and when tasks are personalized ( Glass and Yuill, 2023 ). The current results contribute to a growing body of literature challenging the idea that autistic people have impaired synchrony and demonstrate the importance of task selection in synchrony research.…”
Section: Discussionmentioning
confidence: 99%
“…Our mediating model of motor, EF, and social function could be partially explained by the theory of social movement synchronization (SMS) in autistic population ( 65 , 66 ), which refers to synchronous motor movements within social interaction. The motor-social relationship might be attributed to the deficit of SMS among autistic children, particularly when intentional SMS tasks were involved ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our mediating model of motor, EF, and social function could be partially explained by the theory of social movement synchronization (SMS) in autistic population ( 65 , 66 ), which refers to synchronous motor movements within social interaction. The motor-social relationship might be attributed to the deficit of SMS among autistic children, particularly when intentional SMS tasks were involved ( 65 ). These intentional SMS tasks generally involve additional processing demands, such as attention, working memory and movement planning, posing challenges for autistic individuals with EF difficulties ( 67 ).…”
Section: Discussionmentioning
confidence: 99%